Development of the Quality of Nursing Care Scale for Hospitalized Acute Respiratory Infection Children in Indonesia - Dewi Elizadiani Suza; Busakorn Punthmatharith; Ladawan Prateepchaikul (Universitas Airlangga, 2014)
Introduction: The QNCS-HARIC instrument is expected to be a potential tool for obtaining knowledge about quality of pediatric nursing care with acute respiratory infection (ARI) children and thereby contributing to improve quality in nursing practice with a more genuinely parental involvement approach, especially in Indonesia.Methods: Development of the QNCS-HARIC refers to literature review, expert panel meeting, experts’ review, and pilot study.Results: Four dimensions and 79 items were generated: 1) the physical needs of ARI children (36 items), 2) the psychological needs of ARI children and family (26 items), 3) the socio-cultural needs of ARI children and family (10 items), and 4) the spiritual needs of ARI children and family (7 items). The validity was approved by fi ve experts yielding the content validity index equals to .96. After performing the CVI, the QNCS-HARIC consisted of 78 items (deleting 2 items of the physical needs of ARI children dimension and additional 1 item of the physical needs of ARI children dimension). The reliability was tested with 30 pediatric nurses yielding alpha cronbach’s coeffi cient of the overall QNCS-HARIC 77 items was .94 and each of dimension equal to .94, .87, .79, and .73, respectivelyConclusion: To improve quality of nursing care delivery, pediatric nurses need to be equipped with a quality instrument which should be psychometrically tested, sensitive, specific, accurate, objective, and feasible.